If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2 = 41 Reorder the terms: -2 + 5x = 41 Solving -2 + 5x = 41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 5x = 41 + 2 Combine like terms: -2 + 2 = 0 0 + 5x = 41 + 2 5x = 41 + 2 Combine like terms: 41 + 2 = 43 5x = 43 Divide each side by '5'. x = 8.6 Simplifying x = 8.6
| 8=x*6 | | 5y-2y=30+3-9 | | x+x+2+x+4=39 | | -3+15=-a+5a | | x+x+2x+4=39 | | 14xy-28y= | | x(-8x+6)+5=0 | | 102=x-(-130) | | 7g-5g=8+14 | | 15a+24=-8+15a | | 2w-w=-3-8 | | f(x)=4x-2x^2 | | 2(2+3)=5x-2 | | 2x^2-3y^2=23 | | x+(-22)=-96 | | x-1.14=-22 | | 3x-10x=2.5 | | 446.73=220+0.79 | | -10=2n+1 | | -35+x=4.8 | | 6y-10=4x-6 | | -6(11j+13)=6(-12-12j) | | 15+3c=-6(7c+20) | | x+5.8=-9.5 | | -10+4-15=4m+m-8m | | 6x+1y= | | 2x+3+4x-1=50 | | Y=36x^2+12x+1 | | -6(-4x-2)+5(6x-5)=-13 | | 3x+4=9x+-12 | | (12+8)/(3-2+9)*6= | | -10=d-2 |